Gelatin extraction from chicken skin by conventional and Ohmic heating methods and comparison with commercial halal gelatins - Isik, Cigdem; Parlak, Mahmut Ekrem; Demirel, Fatma Tuba Kirac; Odabas, Halil Ibrahim; Dagdelen, Adnan Fatih; Yilmaz, Mustafa Tahsin; Saricaoglu, Furkan Turker (Elsevier Sci Ltd, 2024)
Gelatin extraction from chicken skins using ohmic heating (OH) is a promising application in the food industry. In this study, the effects of OH parameters (electric field (5, 10, 15, and 20 V/cm) and extraction time (1, 3, and 5 h)) on the extraction yield, physicochemical, functional, rheological, thermal, and microstructural properties of chicken skin gelatin were investigated, as well as comparison with conventional extraction and commercial halal gelatins. Chicken skin gelatins obtained with OH-assisted extraction showed higher ash content resulting in more turbidity than commercial gelatins. OH parameters significantly increased the gelatin yield, and 1 h of OH treatment revealed the highest gel strength amongst the electric field applications, conventional extracted, and bovine gelatin. The melting and gelation temperatures of chicken skin gelatins were higher than bovine gelatin and OH treatment increased the thermal stability. The amino acid composition significantly changed with OH treatment, and total imino acid content, relating to the gelation properties, increased. Functional properties, water and oil binding, emulsifying, and foaming, of chicken skin gelatin were significantly higher than commercial gelatins, and OH treatment significantly increased these properties. Overall, OH extraction of gelatin from chicken skins could be a better option for less extraction time, higher extraction yield, better functionality, and higher thermal stability compared to conventional extraction. It was concluded that chicken skin gelatins extracted using OH have properties that can be an alternative to commercial gelatins, but further purification processes are required.
Keywords: Poultry by-product; Gelatin; Ohmic heating; Halal gelatin; Gel strength